Modeling and analysis of a microresonating biosensor for detection of Salmonella bacteria in human blood - Bahadoran, Mahdi; Ahmad Noorden, Ahmad Fakhrurrazi; Chaudhary, Kashif; Mohajer, Faeze Sadat; Aziz, Muhammad Safwan; Hashim, Shahrin; Ali, Jalil; Yupapin, Preecha P. (Multidisciplinary Digital Publishing Institute (MDPI), 2014)
A new photonics biosensor configuration comprising a Double-side Ring Add-drop Filter microring resonator (DR-ADF) made from SiO2-TiO2 material is proposed for the detection of Salmonella bacteria (SB) in blood. The scattering matrix method using inductive calculation is used to determine the output signal’s intensities in the blood with and without presence of Salmonella. The change in refractive index due to the reaction of Salmonella bacteria with its applied antibody on the flagellin layer loaded on the sensing and detecting microresonator causes the increase in through and dropper port’s intensities of the output signal which leads to the detection of SB in blood. A shift in the output signal wavelength is observed with resolution of 0.01 nm. The change in intensity and shift in wavelength is analyzed with respect to the change in the refractive index which contributes toward achieving an ultra-high sensitivity of 95,500 nm/RIU which is almost two orders higher than that of reported from single ring sensors and the limit of detection is in the order of 1 × 10−8 RIU. In applications, such a system can be employed for a high sensitive and fast detection of bacteria.